2013
DOI: 10.1038/labinvest.2013.83
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblasts endocytose and degrade transthyretin aggregates in transthyretin-related amyloidosis

Abstract: Transthyretin (TTR)-related amyloidosis is a fatal disorder characterized by systemic extracellular deposition of TTR amyloid fibrils. Mutations in the TTR gene cause an autosomal dominant form of the disease-familial amyloidotic polyneuropathy (FAP). Wild-type (WT) TTR can also form amyloid fibrils in elderly patients with senile systemic amyloidosis. Regression of amyloid deposits in FAP patients who undergo liver transplantation to remove the main source of mutant TTR suggests the existence of mechanisms fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0
1

Year Published

2014
2014
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 42 publications
0
24
0
1
Order By: Relevance
“…Recent work from Misumi and colleagues has shown that fibroblasts endocyte and degrade TTR aggregates in vitro and in vivo 47. All together these studies provide evidence for the complex cellular dynamics underlying TTR catabolism and clearance and its impact in the FAP pathology.…”
Section: Discussionmentioning
confidence: 86%
“…Recent work from Misumi and colleagues has shown that fibroblasts endocyte and degrade TTR aggregates in vitro and in vivo 47. All together these studies provide evidence for the complex cellular dynamics underlying TTR catabolism and clearance and its impact in the FAP pathology.…”
Section: Discussionmentioning
confidence: 86%
“…This difference is puzzling. Although exploration of the mechanisms of LC internalization and trafficking is beyond the scope of this interactomic study, we speculate that different rates of uptake/internalization (hCFs possess intense endocytic activity) (25, 26, 61, 62), distinct routes of entry, distinct intracellular trafficking, and, potentially, specific modifications of LCs within cells (25) might render these proteins more amenable to establishing contacts with and penetrating inside mitochondria of specific cells such as hCFs.…”
Section: Discussionmentioning
confidence: 99%
“…However, there was a significant decrease in the amount of prefibrillar hTTR detected in the stomach tissue of animals receiving the C5 receptor agonists when compared to control presumably due to increased phagocytosis of prefibrillar hTTR. The PMX53 group mice exhibited no significant rise in prefibrillar hTTR, compared to control, as might be expected due to reduced phagocytosis of prefibrillar hTTR (Misumi et al, 2013; Suenaga et al, 2016). This is most likely explained by a shift to a higher rate of amyloid formation driven by higher prefibrillar hTTR.…”
Section: Discussionmentioning
confidence: 50%